Recovery in football - Heidari, J.; Loch, F.; Kellmann, M. (Football Psychology - From Theory to Practice, 2019)
Modem elite football requires a myriad of different skills from the players encompassing technical, tacdcal, physical, and psychological capabilities. These demands can exhibit significant stress on the players and need to be balanced by appropriate physiological and psychological recovery in order to maintain a high level of performance. An important prerequisite of recovery interventions consists of the implementation of monitoring routines to assess the specific recovery needs of players and teams. Ideally, a combination of behavioural (e.g. global positioning system), physiological (e.g. blood lactate), and psychological (e.g. questionnaires) instruments for recovery monitoring should be evaluated to enable a detailed picture of the recovery status and the development of individualised recovery interventions. On a physiological level, a recovery protocol entailing rehydration and nutrition, cold water immersion, compression garments, and sufficient sleep should be warranted to promote the physiological recovery process. Psychologically, relaxation techniques can be performed to reduce mental fatigue and should be selected based on the individual preferences. It can be stated that the probability of success in elite football can be significantly increased in case the transfer from scientific knowledge regarding recovery monitoring and interventions can be integrated into practical contexts. The complexity of contemporary elite football suggests an array of different recovery strategies for each player to accomplish optimal functioning. Future research should therefore focus on individual and practice-oriented approaches to both assess and stimulate recovery.